The unseen - Jacobsen, Roy, 1954- (Biblioasis international translation series, 2020)
"Islanders are never afraid, if they were, they wouldn't be able to live here. Born on the island that bears her name, Ingrid Barrøy's world is circumscribed by storm-scoured rocks and the moods of the sea by which her family lives and dies. But her father dreams of a bridge, and her mother longs for her own childhood island, and Norway faces its own sea change: the advent of a modern world and its attendant unpredictability and violence. Brilliantly translated into English by Don Bartlett and Don Shaw, The Unseen is a profound exploration of family, resilience, and fate."--